The role of Vps4 in cancer development - Huang, Li Juan; Zhan, Shi Tong; Pan, Yu Qin; Bao, Wei; Yang, Ye (Frontiers in Oncology, 2023)
VPS4 series proteins play a crucial role in the endosomal sorting complexes required for the transport (ESCRT) pathway, which is responsible for sorting and trafficking cellular proteins and is involved in various cellular processes, including cytokinesis, membrane repair, and viral budding. VPS4 proteins are ATPases that mediate the final steps of membrane fission and protein sorting as part of the ESCRT machinery. They disassemble ESCRT-III filaments, which are vital for the formation of multivesicular bodies (MVBs) and the release of intraluminal vesicles (ILVs), ultimately leading to the sorting and degradation of various cellular proteins, including those involved in cancer development and progression. Recent studies have shown a potential relationship between VPS4 series proteins and cancer. Evidence suggests that these proteins may have crucial roles in cancer development and progression. Several experiments have explored the association between VPS4 and different types of cancer, including gastrointestinal and reproductive system tumors, providing insight into the underlying mechanisms. Understanding the structure and function of VPS4 series proteins is critical in assessing their potential role in cancer. The evidence supporting the involvement of VPS4 series proteins in cancer provides a promising avenue for future research and therapeutic development. However, further researches are necessary to fully understand the mechanisms underlying the relationship between VPS4 series proteins and cancer and to develop effective strategies for targeting these proteins in cancer therapy. This article aims to review the structures and functions of VPS4 series proteins and the previous experiments to analyze the relationship between VPS4 series proteins and cancer.